Betting on you - Painter, Lynn (2023)
"When seventeen-year-old Bailey starts a new job at a hotel waterpark, she is less than thrilled to see an old acquaintance is one of her coworkers. Bailey met Charlie a year ago on the long flight to Omaha, where she moved after her parents' divorce. Charlie's cynicism didn't mix well with Bailey's carefully well-behaved temperament, and his endless commentary was the irritating cherry on top of an already emotionally fraught trip. Now, Bailey and Charlie are still polar opposites, but instead of everything about him rubbing Bailey the wrong way, she starts to look forward to hanging out and gossiping about the waterpark guests and their coworkers--particularly two who keep flirting with each other. Bailey and Charlie make a bet on whether or not the cozy pair will actually get together. Charlie insists that members of the opposite sex can't just be friends, and Bailey is determined to prove him wrong. Bailey and Charlie keep close track of the romantic progress of others while Charlie works to deflect the growing feelings he's developed for Bailey. Terrified to lose her if his crush becomes known, what doesn't help his agenda is Bailey and Charlie "fake dating" in order to disrupt the annoying pleasantries between Bailey's mom and her mom's new boyfriend. Soon, what Charlie was hoping to avoid becomes a reality as Bailey starts to see him as not only a friend she can rely on in the midst of family drama--but someone who makes her hands shake and heart race. But Charlie has a secret--a secret that involves Bailey and another bet Charlie may have made. Can the two make a real go of things...or has Charlie's secret doomed them before they could start?" --
Ages 14 up.
Grades 10-12.
Keywords: Interpersonal relations -- Juvenile fiction; Friendship -- Juvenile fiction; Wagers -- Juvenile fiction; Occupations -- Juvenile fiction; High school students -- Fiction; Young adult fiction; Interpersonal relations -- Fiction; Friendship -- Fiction; Wagers -- Fiction; Occupations -- Fiction; Omaha (Neb.) -- Fiction; Romance fiction; Novels